Influence of Fixed Temperature of Chilled Water Outlet Setting toward Performance of Chiller Absorbtion with Two Level Heating Cycle Method - I Gusti Agung Bagus Wirajati; Made Sucipta (Jurnal Energi Dan Manufaktur, 2009)
The study investigated the performance of re-heat two stage cycle. This paper presents the working principle and theexperimental results of the reheat two stage adsorption cycle. The performance of the cycle was evaluated under differentheat source temperature and mass recovery time. Coefficient of performance (COP) and cooling capacity have beencalculated to analyze the influences of experimental conditions. The experimental results shown in both COP and coolingcapacity increased along with heat source temperature increased, and mass recovery time is very effective to improve theperformance without increasing heat source temperature.